Adam Stephen papers - Stephen, Adam.
Correspondence, accounts, legal papers, survey reports, and plats relating to Stephen's militia service in Virginia during the colonial period and with the 4th Virginia Regiment and the Continental Army during the Revolution and to the operation of his plantation. Correspondents include Robert Dinwiddie, Francis Fauquier, Enoch Innis, Thomas Bryan Martin, William Maxwell, Angus McDonald, James Mercer, John Russell, Alex Stephen, Alexander Stuart, and George Washington.
Microfilm edition available
Microfilm of originals in the Manuscript Division.
Planter and military officer of Berkeley County, Va. (later W. Va.). Born circa 1730, died 1791.
Collection material in English.
Stephen's letter (1777 March 15) to Angus McDonald was formerly cataloged separately as part of the Miscellaneous Manuscripts Collection.
Keywords: Dinwiddie, Robert, -- 1693-1770 -- Correspondence; Fauquier, Francis, -- 1704?-1768 -- Correspondence; Innis, Enoch -- Correspondence; Martin, Thomas Bryan -- Correspondence; Maxwell, William, -- 1733?-1796 -- Correspondence; McDonald, Angus, -- active 1777 -- Correspondence; Mercer, James, -- 1736-1793 -- Correspondence; Russell, John, -- active 1765-1766 -- Correspondence; Stephen, Alex -- Correspondence; Stuart, Alexander, -- 1733-1822 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; United States. -- Continental Army. -- Virginia Infantry Regiment, 4th; Plantations -- Virginia; Berkeley County (W. Va.) -- History; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Revolution, 1775-1783 -- Campaigns; Virginia -- History -- Colonial period, ca. 1600-1775.; Virginia -- History -- Revolution, 1775-1783.; Virginia -- Militia; Army officers